Annealing Effect on Some Optical Properties of Cr2O3 Thin Films Prepared by Spray Pyrolysis Technique - Baghdad Science Journal (مجلة بغداد للعلوم)
Cr2O3 thin films have been prepared by spray pyrolysis on a glass substrate. Absorbance and transmittance spectra were recorded in the wavelength range (300-900) nm before and after annealing. The effects of annealing temperature on absorption coefficient, refractive index, extinction coefficient, real and imaginary parts of dielectric constant and optical conductivity were expected. It was found that all these parameters increase as the annealing temperature increased to 550°C.